Evaluasi Penggunaan Media Pembelajaran E-Learning pada Mata Pelajaran IPS Era Pandemi Kelas IX di SMP Islam Al Azhar 38 Wonosari Kabupaten Gunungkidul - Akhmad Shatiri; Sukadari Sukadari (UM Purwokerto Press, 2022)
This study aims to describe the evaluation of the use of e-learning-based learning media in social studies subjects in the era of the epidemic of class IX at Al Azhar 38 Islamic Junior High School, Wonosari, Gunungkidul Regency. This study uses a qualitative method with a case study approach. The sources of data in this study were teachers, parents and students of class IX Islamic Junior High School Al Azhar 38 Wonosari, Gunungkidul Regency. Several data collection techniques used in this study were interviews, observations and online documentation. The results of this study are (1) to describe various types of e-learning learning media that are relevant for learning social studies subjects. (2) The advantages and disadvantages of e-learning-based evaluation media. (3) Other findings in this study indicate an evaluation model of the use of e-learning media in social studies learning that has been implemented including portfolio-based and project-based evaluations. However, it is undeniable that in the application of the alternative evaluation model there are several constraining factors faced, namely the lack of enthusiasm of parents and students, knowledge of parents in the application of the evaluation model, and the lack of cooperation between teachers and parents.